Personalized nursing interventions based on risk factors for post-traumatic stress disorder following intracerebral hemorrhage: an analysis of effectiveness - Bu, Chen; Zhang, Qinyun; Xu, Liang (Frontiers in Psychiatry, 2025)
BackgroundThis study aimed to identify independent risk factors for post-traumatic stress disorder (PTSD) in intracerebral hemorrhage (ICH) patients and to assess the clinical effectiveness of personalized nursing interventions tailored to these risk factors.MethodsNinety-one ICH patients with PTSD and 76 without PTSD admitted from January 2023 to January 2025 were included in the study. A retrospective analysis was performed to determine the factors associated with the development of PTSD in ICH patients and to develop targeted and individualized care strategies. Subsequently, a prospective cohort of 98 consecutive patients with ICH and PTSD were randomly assigned to either a targeted care group (n=49) or a usual care group (n=49). After 7 patients were lost to follow-up in the targeted care group, 42 patients in the observation group and 49 in the control group were included in the final analysis. Outcomes were measured using the Barthel Index (BI), Connor-Davidson Resilience Scale (CD-RISC), and SF-36 quality of life assessment.ResultsUnivariate analysis revealed a higher proportion of patients with hemorrhage involving the amygdala, hippocampus, or prefrontal cortex (P<0.05), as well as younger age, lower education, and poorer baseline CD-RISC and BI scores in the PTSD group. Multivariate regression analysis confirmed that brain region injury, low education level, low CD-RISC score, and low BI were independent risk factors for PTSD (P<0.05). The observation group (n=42) demonstrated superior outcomes in psychological resilience (CD-RISC), functional independence in daily living (BI), and quality of life (SF-36 physical function, social function, role emotional domains; all P<0.05). Patient satisfaction was significantly higher in the observation group (90.48%, P<0.05).ConclusionPTSD following ICH is strongly associated with specific neuroanatomical damage, limited education, impaired psychological resilience, and functional disability. Our biopsychosocial model-based personalized nursing protocol effectively enhances psychological resilience, daily functioning, and overall quality of life in this patient population.